The new medicine [videorecording (DVD)] - Meyer, Muffie; Schreiber, Liev; Reeve, Dana (First Run Features, 2006)
A documentary exploring a burgeoning movement taking place in hospitals and clinics across the country: integrating the best of high-tech medicine with a new attitude that recognizes it is essential to the healing process to treat the patient as a whole person, and not a cog in an assembly line.